Analisis Pengaruh Kepuasan Kerja, Komitmen Organisasi, dan Keterlibatan Kerja Pada Kinerja Karyawan Bank Muamalat Surakarta - Agus Marimin; Harun Santoso (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study was to examine the positive effect of job satisfaction, organizational commitment, and job involvement on employee performance at Bank Muamalat Surakarta. This research methodology using explanatory research type, the researcher conducted a survey and jumped into the research location by giving questionnaires to the employees of Bank Muamalat Surakarta directly. This study uses a quantitative method, where this method is used to test the hypothesis. The population of this research is all employees of Bank Muamalat Surakarta as many as 60 people as well as the research sample. The sampling technique used total sampling technique, where the number of samples was the same as the population. The data analysis technique used multiple regression analysis, t test, F test, and R2 test. The results showed that there was a significant influence between job satisfaction factors (X1) on the employee performance of Bank Muamalat Surakarta, there was a significant influence between organizational commitment factors (X2) on the employee performance of Bank Muamalat Surakarta, there was a significant influence between job involvement factors (X3) on the performance of employees of Bank Muamalat Surakarta.